Anaphylaxis in children - Cichocka-Jarosz, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Anaphylaxis, though rare, is an increasing emergency especially in children and remains under-diagnosed and undertreated. Boys outnumber girls by 3 : 2 in preschool children, but from the age of 15 females predominate. Food is the main trigger of anaphylaxis in children with the commonest being nuts and milk. The diagnosis is primarily based on the clinical history and clinical criteria. The most to less frequent symptoms concern dermatological, respiratory, gastrointestinal and cardiovascular ones, respectively. Emergency management requires the life support ABCDE approach. Intramuscular adrenalin, repeated as required, is a drug of choice in the case of a severe systemic reaction. Intravenous fluids, oxygen and a certain position of the patient are the next steps of the treatment. When recovered, at the discharge from hospital, the child should be given a prescription for auto-injection with adrenalin and trained (together with his family) how to use it. After a systemic reaction it is obligatory to refer the child to a specialist allergy clinic for careful diagnosis. There is a necessity of constant education and regular assessment of doctors, nurses, patients and their families for adherence with present recommendations.